FROM OWNERSHIP TO ENTITLEMENT: REPLACING THE BILLS OF LADING ACT 1855 WITH THE CARRIAGE OF GOODS BY SEA ACT 1992 - Lam, Nguyen Tung; Anh, Truong Quach Ngoc; Anh, Hoang Thi Lan; Ha Linh, Nguyen (International Journal of Research -GRANTHAALAYAH, 2025)
This paper explores the significance and evolution of the Bill of Lading (BoL) in maritime law. A BoL presumes the existence of a contract of carriage, either written or implied, and traditionally fulfills three key roles: serving as a receipt for cargo, providing evidence of a contract of carriage, and acting as a document of title. The Bills of Lading Act 1855 (BoLA) governed the transfer of contractual rights, linking them to the transfer of property in goods. However, the Act faced practical challenges when BoL holders did not possess ownership of the goods. The 1991 Report by the Law Commission of England and the Scottish Law Commission highlighted numerous issues with the BoLA 1855, including its limited applicability and outdated provisions. These deficiencies led to its repeal and replacement by the Carriage of Goods by Sea Act (COGSA) 1992, which addressed key problems by granting contractual rights to consignees independent of property transfer.